Do intangible assets stimulate firm performance? Empirical evidence from Vietnamese agriculture, forestry and fishery small- and medium-sized enterprises - Tuan Nguyen-Anh; Hoang Duc Chinh; Linh Nguyen-Thi-Thuy; Vuong Vu-Tien; Uyen Nguyen-Dinh; Nguyen To-The (Journal of Innovation & Knowledge (JIK), 2022)
Innovation and intangible asset (IA) management have not received adequate attention amongst labour- and capital-intensive sectors. This study investigates the effect of IAs on firms' performance and the internal and external determinants of firms' IA development amongst small- and medium-sized enterprises (SMEs) in the Vietnamese sectors of agriculture, forestry and fishery (AFF). The study adopts a stochastic frontier analysis to estimate firms' performance and propensity score matching to examine the difference between firms with and without IAs. Ten hypotheses of innovation determinants including firms' internal and external factors are also investigated. The results reveal three notable findings. (1) For Vietnamese AFF sectors, IAs diminish firms' performance. (2) Internal factors such as age, size and financial robustness have positive effects on the formation of IAs, while investments in land, labour and research and development impose mixed effects. (3) External factors, such as regional and province-specific characteristics, have significant impacts on IAs. These results suggest a review of current policies on innovation and IA management amongst SMEs.
Keywords: C31; D24; O13O30; Q16; 650; Agriculture; Fishery; Forestry; Innovation; Intangible assets; Propensity score matching; Technical efficiency; Vietnam